Gladiolus izzet-baysalii (Iridaceae, Crocoideae), a new species from Turkey - Eker, İsmai̇l; Sağiroğlu, Mehmet (Phytotaxa, 2021)
Gladiolus izzet-baysalii is described and illustrated as a new species from Karaman province in Southern Anatolia. Gladiolus izzet-baysalii is not morphologically close to any of the species of Gladiolus in Turkey. Although it has some similarities with G. illyricus and G. hamzaoglui in terms of habitus, G. izzet-baysalii differs significantly in tunic structure, number of leaves, inflorescence, perianth, anther, style, capsule and seed features. In this study, the diagnostic morphological features, distribution, conservation status, habitat and ecological characteristics of the new species are discussed. Micromorphological characteristics of G. izzet-baysalii, G. illyricus and G. hamzaoglui seeds are also examined and compared using stereomicroscope and SEM analyses.